Sucesso profissional: escolhas duradouras em tempos de incerteza - Carvalho, Débora Gusmão Telles de (2020)
In the current Brazilian scenario, we can find dissatisfied people regarding their jobs. Often, even after devoting time and money to achieve specific higher-level career, they become frustrated and follow a parallel path in another activity that gives them more pleasure. Others choose to continue in their chosen profession, though far from finding any meaning on it. On the other hand, there are those who are still working on something related to their major and are pleased with the choice they once made, finding success in the practice of their profession. This research aimed, through a systemic approach, to analyze the factors involved in the decision-making process, when it comes to choosing a profession, in order to understand which ones tend to provide the individual with a lasting choice. For this, we adopted the mixed method one, with a quantitative phase with the appliance of 231 electronic questionnaires from the EPSCR (Career Success Perception Scale) validated by Costa, (2013). Subsequently, a qualitative study was conducted, with semi-structured interviews with six collaborators, selected from the results obtained in the first phase of the research. Through the analyzes, it was possible to conclude that factors such as the valorization of study and work, identifications with a close figure, Self differentiation and the quality of intrafamily communication tend to contribute to the professional choice. Furthermore, we were able to find evidence that the professional system is quite vulnerable to traditional gender constructions still in force in Brazilian society. We believe that, considering these factors, the study contributes to clinical psychology area, in the development of strategies that can promote more conscious and lasting professional choices